2005
DOI: 10.3201/eid1112.050752
|View full text |Cite
|
Sign up to set email alerts
|

SalmonellaandCampylobacterspp. in Northern Elephant Seals, California

Abstract: Campylobacter and Salmonella spp. prevalence and antimicrobial drug sensitivity were determined in northern elephant seals that had not entered the water and seals that were stranded on the California coast. Stranded seals had a higher prevalence of pathogenic bacteria, possibly from terrestrial sources, which were more likely to be resistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 8 publications
1
44
1
Order By: Relevance
“…This prompted a two-year study to investigate the prevalence of Campylobacter in both free-ranging and stranded northern elephant seals in northern California (23). C. jejuni, C. lari, and a novel Campylobacter sp.…”
mentioning
confidence: 99%
“…This prompted a two-year study to investigate the prevalence of Campylobacter in both free-ranging and stranded northern elephant seals in northern California (23). C. jejuni, C. lari, and a novel Campylobacter sp.…”
mentioning
confidence: 99%
“…and C. jejuni isolated from 195 seals used in this study were previously reported, 23 with one additional seal in this study that was not culture positive for either bacterium. A total of 73 seals harbored Salmonella spp.…”
Section: Bacterial Isolationmentioning
confidence: 99%
“…Salmonella spp. and C. jejuni were isolated as previously described, 23 using standard techniques. 24,25 Antimicrobial sensitivity testing Antimicrobial susceptibility was performed on up to three E. coli isolates from each fecal sample using the broth microdilution method following the Clinical and Laboratory Standards Institute (CLSI) methods 26 using Sensititre ® Automated Microbiology Systems.…”
Section: Bacterial Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Campylobacter insulaenigrae was isolated from three harbor seals (Phoca vitulina) and a harbor porpoise (Phocoena phocoena) in Scotland (7). The isolation of C. jejuni, C. lari, and an unknown Campylobacter species from juvenile northern elephant seals (Mirounga angustirostris) in California was also reported (22). Finally, 71 isolates of C. insulaenigrae and 1 isolate similar to but distinct from both Campylobacter upsaliensis and Campylobacter helveticus were isolated from northern elephant seals in California (23).…”
mentioning
confidence: 95%